Atomic structure transition for various solidification paths of Pd40Ni40P20 at different cooling rates. (October 2022) - Yu, Pengfei; Xia, Mingxu; Han, Xiujun; Cao, Saichao; Zhao, Yimeng; Zeng, Long; Li, Jianguo
Abstract: Demonstrating the cooling rate effect on the solidification path is a massive challenge. In this paper, the atomic structure of the Pd40 Ni40 P20 melt was statistically "snapped" at different temperatures with two different cooling rates. The structure evolution was analyzed with in situ high-energy X-ray diffraction method and Reverse Monte Carlo simulation. It indicates that the presence of Liquid-Liquid Phase Transition (LLPT) makes the melt more inclined to form crystal but the higher cooling rate leads to an insufficient transition retaining more icosahedral-like clusters. This work provides dynamic guidance for understanding the competition between crystallization and vitrification. Graphical abstract: Image, graphical abstract